Study of thermoelectric generators for pulse and normal conditions - Chen, Pei Yi (Nanyang Technological University, 2020)
Energy, a highly valuable resource, is indispensable in our everyday lives. Amongst the different kinds of energy available, electrical energy continues to position itself as the ‘’fuel’ of the future. One method to harvest energy will be through the conversion of heat flux into electricity. Thermal energy is present in many of our industrial processes and the heat produced is usually lost and wasted. The technology of converting heat to electricity is performed by a thermoelectric generator (TEG) is very interesting as the system is easy to handle, free of moving parts and environmentally friendly. This project aims to improve the efficiency of TEG by operating the thermoelectric module under transient conditions. The temperature on the hot junction of the thermoelectric module is varied while maintaining a constant cold junction temperature. By varying the hot junction temperature and duration of the cycles, the thermoelectric module is subjected to different modes of pulsing. The conversion efficiencies subjected to these pulses are studied. By the addition of more heat energy during pulsing periods and less amount of heat during non-pulsing periods, the performance of TEG can be improved. This project shows these phenomena experimentally as a proof-of-concept. By employing pulsing and non-pulsing methodology, the heat is recovered for the nest pulsing mode, which also prevents the utilized energy (for electricity generation) from Joule heating and Thomson effects. Therefore, the overall efficiency is improved with the reduction of input heating effects. The thermoelectric-material properties are not changed. The proposed TEG transfers heat energy from exhaust waste gas produced by iron or steel factories to Dowtherm T.